2003
DOI: 10.1002/ps.728
|View full text |Cite
|
Sign up to set email alerts
|

United States Department of Agriculture—Agricultural Research Service research on alternatives to methyl bromide: pre‐plant and post‐harvest

Abstract: Methyl bromide is a widely used fumigant for both pre‐plant and post‐harvest pest and pathogen control. The Montreal Protocol and the US Clean Air Act mandate a phase‐out of the import and manufacture of methyl bromide, beginning in 2001 and culminating with a complete ban, except for quarantine and certain pre‐shipment uses and exempted critical uses, in January 2005. In 1995, ARS built on its existing programs in soil‐borne plant pathology and post‐harvest entomology and plant pathology to initiate a nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(90 citation statements)
references
References 40 publications
0
88
0
2
Order By: Relevance
“…To determine the number of colony forming units of Pythium, 1 g of airdried soil was added to 10-ml sterilized water blanks (triplicate tubes for each sample), vortexed to mix the soil, and 500 µl of this soil solution was distributed evenly over a petri dish containing a semiselective Pythium medium (five plates per tube). The medium consisted of corn meal agar (17 g/liter, BBL, Kansas City, MO) amended immediately after autoclaving with 0.1% Tween 20 followed by pimaricin (10 mg/liter), ampicillin (250 mg/liter), rifampicin (10 mg/liter), rose bengal (50 mg/liter), and Benomyl 50WP (28). After 24 h incubation at 25°C, the surfaces of the plates were washed free of soil under a gentle stream of water and the number of colonies counted.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the number of colony forming units of Pythium, 1 g of airdried soil was added to 10-ml sterilized water blanks (triplicate tubes for each sample), vortexed to mix the soil, and 500 µl of this soil solution was distributed evenly over a petri dish containing a semiselective Pythium medium (five plates per tube). The medium consisted of corn meal agar (17 g/liter, BBL, Kansas City, MO) amended immediately after autoclaving with 0.1% Tween 20 followed by pimaricin (10 mg/liter), ampicillin (250 mg/liter), rifampicin (10 mg/liter), rose bengal (50 mg/liter), and Benomyl 50WP (28). After 24 h incubation at 25°C, the surfaces of the plates were washed free of soil under a gentle stream of water and the number of colonies counted.…”
Section: Methodsmentioning
confidence: 99%
“…Methyl bromide is a critical element in the pre-plant management of soil-borne pests and pathogens in high value fruit, nursery and ornamental crops, and in post-harvest management of pests on fresh produce and durable commodities (Schneider et al 2003). Since the early 1990s, this fumigant has been known to break down under the influence of strong UV rays, and thus release bromide atoms which deplete the ozone layer (WMO 1995;Dabrowski 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Since the early 1990s, this fumigant has been known to break down under the influence of strong UV rays, and thus release bromide atoms which deplete the ozone layer (WMO 1995;Dabrowski 2002). Increased awareness of the effect of chemicals on the environment and non-target organisms (Horowitz et al 2003;Cuthbertson and Murchie 2005, 2010, 2012 and the phase-out of methyl bromide in industrialised countries in January 2005 (Schneider et al 2003) has lead to a greater demand for alternatives to methyl bromide for invertebrate pest control to be devised (Giannakou and Karpouzas 2003;Lopez-Aranda et al 2003;Slusarski and Pietr 2003). Under current UK quarantine and pre-shipment rules methyl bromide can be used in an emergency situation if no viable alternative can be found.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of such treatments have relied on methyl bromide (Lopez-Aranda et al, 2003;Walters, 2001). However, although methyl bromide usage for quarantine purposes is exempt from being phased out (Schneider et al, 2003) if no viable alternative is found, there is still a demand for alternatives to methyl bromide for invertebrate pest control to be devised (Giannakou and Karpouzas, 2003;Lopez-Aranda et al, 2003;Slusarski and Pietr, 2003).…”
Section: Introductionmentioning
confidence: 99%